Response of Triticum aestivum cultivars to salt stress with reference to different biochemical attributes - Gul, Humaira; Nazeer, Hina; Khan, Aqib; Khushnood Ur Rehman; Saddiq, Ghulam; Iftikhar, Muhammad; Butt, Zahid Ali (Journal of Pure and Applied Agriculture, 2024)
Different abiotic stresses, especially salinity and drought predicted to be increase with global change. Most of the soil degradation caused through this salt stress has a major negative impact on crops growth and production, particularly in the world’s arid and semi-arid regions. Wheat (Triticum aestivum) is an important food-crop in Pakistan and contributes 60 % of dietary supplement for human being. Production of this crop can be enhanced up-to marginal and moderately salt affected areas through using salt tolerant varieties of this crop. Present investigation highlighted this aim through using six local wheat varieties for screening their salt tolerance in terms of biochemical traits such as photosynthetic pigments, primary metabolites, secondary metabolites, antioxidant enzyme activities and endogenous hormones level of Triticum aestivum cultivars. The experiment was completely randomized design and six selected Triticum aestivum varieties, were irrigated with NaCl (0 and 150 mM). Salinity exposure causes degradation in chlorophyll and reduction in endogenous IAA level under high salt application. Furthermore, obtained results indicated that ratio of chlorophyll, total carotenoids, carbohydrates, proteins, lipids, phenols, as well as lycopene and proline, antioxidant, ascorbate-peroxidase, catalase, flavonoids, lipid-peroxidation, tannins, β-carotene, guaiacol-peroxidase endogenous ascorbic acid and salicylic acid increase with increasing salinity. Results of present research suggested that wheat variety F. Sarhad is more tolerant. Further, this variety must be tested in the fields of salt affected areas for better yield.